El periodista ante el secreto del sumario - CERDÁN ALENDA, Manuel (CIC. Cuadernos de Información y Comunicación, 2010)
The proliferation in the media of news from judicial investigations has led to a conflict of interest between judges and journalists. Mainly as a result of the case known as Gürtel, which instructs the High Court of Justice of Madrid against political corruption. Judges require compliance with a summary secret in order to not obstruct their inquiries and to preserve the fundamental rights of the accused, such as the right to privacy and presumption of innocence. The journalists are resisting the claim of some judges to prohibit certain information about their court cases. They see this claim as a cut to the right to information of citizens. This article examines the legal framework that exists in Spain for journalists and the various judgments of the Supreme, Constitutional and European Court of Human Rights have established case law. The authos shows that there are some loopholes and that cohabitation between judges and journalists may be possible.